Analysis of the Influence of Outside Patient Satisfaction (Study at RS X in West Jakarta) - Richo Ryanto Raharjo; Vidya Paramita; Bernarto Innocentius (Budapest International Research and Critics University, 2021)
The objective of this study is to analyze the effect of location, price, and service quality on patient’s satisfaction in X Hospital in West Jakarta. This study uses a quantitative approach using purposive sampling technique. There were 200 respondents included in the study. The data were collected by using questionnaire with a Likert scale and then processed with the Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis technique utilizing the SmartPLS 3.0 program. This study showed that there are positive and significant effect from location, price, and service quality on patient’s satisfaction in X Hospital at West Jakarta. This finding indicates that hospitals with qualified services, together with adequate location and affordable price can optimize patient’s satisfaction.